Understanding the determinants of business intelligence system adoption stages an empirical study of SMEs - Puklavec, Borut (2019)
Puklavec, B., Oliveira, T., & Popovič, A. (2018). Understanding the determinants of business intelligence system adoption stages an empirical study of SMEs. Industrial Management and Data Systems, 118(1), 236-261. https://doi.org/10.1108/IMDS-05-2017-0170